(untitled) (Latakia University Journal -Biological Sciences Series, 2015)
تناول البحث دراسة توزع أفراد النوع Patella caerulea في أربعة مواقع من شاطئ مدينة اللاذقية، تختلف عن بعضها بعضاً تبعاً لطبيعة المستند القاعي ولدرجة تعرضها لمصادر التلوث، وهي مناطق: أفاميا (A) وابن هاني (B) ومرفأ الصّيد في برج إسلام (C) والشّاطئ الرملي في برج إسلام (D). تمّت هذه الدّراسة من الفترة الممتدة من شهر كانون الثّاني 2012 وحتى شهر كانون الثّاني.2013 جمعت العينات يدوياَ من المنطقة فوق الشّاطئية Supralittoral والشّاطئية Littoral وتحت الشّاطئية Sublittoral حتى عمق مترين، أظهرت نتائج هذه الدّراسة الآتي : 1 - تعدُّ المنطقة A أكثر المناطق المدروسة ملائمة لنمو أفراد النوع Patella caerulea وتكاثرها إذ سجلت فيها القيمة العليا للكتلة الأحيائية وبلغت (3990.2 gr/m²) وعدد الأفراد (2128 ind/m²). 2 - سجلت في المنطقة C القيمة الدنيا للكتلة الإحيائية(2872.47 gr/m² ) وعدد الأفراد ind/m² (1632) 3 - يعدّ نوع Patella caerulea من الأنواع الواسعة في مجال التكيف البيئيEurybiont ، إذ وجد في جميع مواقع الدّراسة . 4 – أمَّ النوع Patella caerulea فيعدُّ من الأنواع المهمّة اقتصادياً . This research is a study of distribution of Patella caerulea in four locations of the Latakia shore different from each other by Substrate nature and their exposure to pollution sources. They are as follow : Afamia (A),Ibn Hani (B) ,harbor fishing of Tower Islam (C), and the sandy beach of Tower Islam (D). This study was achieved between January 2012 and January 2013 ,The samples were collected manually from the Supralittoral , Littoral and Sublittoral region(depth of two meters).The results of this study showed the following: 1 – The area A is the most suitable for the growth and reproduction of the Patella caerulea, which recorded the highest value of biomass reaching ( 3990.2 gr / m²), and the number of individuals (2128 ind /m²) . 2 - The area C recorded the lowest value of biomass (2872.47 gr/ m²) and the number of individuals (1632 ind / m²). 3 - Patella caerulea is consederied a Eurybiont as it was found in all the study areas . 4 - Patella caerulea is comercially important species .